Unit for Electro-Magnetic Surfacing of Machine Parts - A. V. Miranovich; Z. A. Mrochek; L. M. Kozhuro (Наука и техника)
Results of the investigations pertaining to electro-magnetic surfacing while reconditioning surfaces of machine parts and design features of the specialized unit are given in the paper. The paper considers technological process and analyses results of system component usage with various magnet design.